THE INFLUENCE OF THE EMPLOYEES’ COMPETENCE AND WORK DISCIPLINE ON PUBLIC SERVICES AT THE DUNGALIYO SUB-DISTRICT OFFICE GORONTALO REGENCY - Susanty Lasena; ELLYS RACHMAN; JUCHRI ABDUSSAMAD (LP2M Universitas Bina Mandiri Gorontalo, 2022)
ABSTRACT Susanty Rusdin Lasena. The Influence of The Employees’ Competence and Work Discipline on Public Services at the Dungaliyo Sub-District Office, Gorontalo Regency (Advisory Commission by Dr. Hj. Ellys Rachman, S.Sos, M.Si and Dr. H Zuchri Abdussamad, S.I.K, M.Si). This study aims to determine and analyze the influence of The Employees’ Competence and Work Discipline on Public Services at the Dungaliyo Sub-District Office, Gorontalo Regency. The method used in this research is quantitative data analysis by using multiple linear regression analysis model and primary data sources. The population in this study were all employees at the Dungaliyo Sub-District Office, Gorontalo Regency, consist of 24 employees. By using a total sampling, 24 respondents were obtained and the community was directly represented by 20 people. Overall population or research respondents are 44 people. The results of the study indicate that competence and work discipline can improve public services. The better the competence and work disciplinewill affect the public services. Based on the analysis results show that the variables of competence and work discipline simultaneously have a significant effect on public services. The variable that has the dominant influence on public services is work discipline. This shows that the higher of the motivation carried out by employees, the higher of the performance showed by them.